SOCIO-ENVIRONMENTAL EXPERIENCES AND PERCEPTIONS OF ELEMENTARY STUDENTS FROM PATOS, PARAÍBA, ON ASPECTS RELATED TO SOLID WASTE - Larrissa Araújo Santos; Jamylle Maria Santos Medeiros; André Higor dos Santos Tavares; Habyhabanne Maia Oliveira; Edevaldo Silva (REVISTA CEREUS, 2016)
The inclusion of environmental issues in schools is essential for students to become social actors aware of the current environmental problems. The objective of this research was to have a didactic experience and assess the knowledge about solid waste with students (N = 72) of two public elementary school in Patos, Paraíba. The research had two distinct phases: a didactic experience on solid waste and; assessment of the students’ perception about Environmental Education and solid waste through interviews with a questionnaire. The didactic experience provided a dialogic and participatory moment with students, encouraging a reflective discussion and presenting the basic knowledge on the subject. The students said they knew more about the selective waste collection (63.8%) and the 4 R’s (48.6%). However, 43.1% had little or no knowledge about dry “trash”, which can hinder proper selective collection. Among the environmental problems related to solid waste, they highlighted diseases (32.4%) and pollution in general (19.9%) and tended to confuse the concept of “trash” with the usefulness of the object (31.9%) and the reuse of recyclable materials (19.4%). The knowledge of the students reported the need to include Environmental Education in school, in a continuous, conceptual way and that provides the students more criticality and reflection on solid waste management. Their interest during the didactic experience confirms their interest in the area, which facilitates the approach and the teaching-learning process.